Survey of the Petroleum hydrocarbon-degrading capacity of three bacteria strains isolated from the oil sludge in Vietnam - Huu, Nguyen Ba; Nga, Vu Hong; Cam Ha, Dang Thi (Academia Journal of Biology, 2015)
Three petroleum hydrocarbon-degrading bacterial strains were isolated from oil sludge of the K130 gasoline and oil storage in Northern Vietnam and designed as HK-T3F1, HK-HF6 and HK-B31. Based on the morphological, physiological characteristics and results of API 20E tests, we proposed that two strains HK-T3F1 and HK-HF6 should be placed to genus Pseudomonas. These bacterial strains grew optimally in mineral medium contained 5% fuel oil or heavy crude oil at 28-37oC, 0-0,5% NaCl and pH = 7. The strain HK-HF6 degraded 76.25% total fuel oil, 84.04% saturated hydrocarbon fractions, 77.33% aromatic hydrocarbon fractions, 51.43% resin and 64.86% asphanten. The strain HK-B31 degraded 57.47% total fuel oil, 78.87% saturated hydrocarbon fractions, 72% aromatics hydrocarbon fractions, 22.86% resin and 24.32% asphanten. Two of three strains were utilized long chain hydrocarbons, resin and asphanten in fuel oil. Especially, the HK-B31 was utilized pristane, and long chain alkanes including hexadecane, eicosane and ocosane such as sole carbon and energy sources.